2021
DOI: 10.1007/s12264-021-00640-9
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Cortical Glial Cell Development

Abstract: Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1+EGFR+ apical multipotent intermediate progenitors (MIPCs), which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
134
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(142 citation statements)
references
References 95 publications
7
134
1
Order By: Relevance
“…Taken together, Li et al [7] clearly demonstrated a common lineage of cortical astrocytes and oligodendrocytes. In general, after the generation of PyNs, the cortical RGCs change their properties to aMIPCs around E16.5, and then quickly transform into proliferative bMIPCs.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…Taken together, Li et al [7] clearly demonstrated a common lineage of cortical astrocytes and oligodendrocytes. In general, after the generation of PyNs, the cortical RGCs change their properties to aMIPCs around E16.5, and then quickly transform into proliferative bMIPCs.…”
mentioning
confidence: 77%
“…In this issue, Li et al [7] took a big step forward in deciphering cortical gliogenesis with a combination of sophisticated molecular approaches. In the mouse cerebral cortex, radial glial cells (RGCs) give rise to different types of glutaminergic pyramidal neurons (PyNs) from E11.5 to E16.5 either directly or indirectly though intermediate progenitor cells (IPCs) [8].…”
mentioning
confidence: 99%
See 3 more Smart Citations